Evaluating a Guidance Counsellor Education Programme: The Methodological Complexities. (2nd June 2015) - Liston, J.; Geary, T.
Abstract: The focus of this paper is on the methodological considerations of a PhD study which evaluated a guidance counsellor education programme, offered by a University in Ireland. The programme is offered as a two-year part-time course, which is delivered over four semesters and two summer schools.Good practice and areas for improvement were identified, acknowledged and affirmed throughout the study. However in doing so a number of methodological complexities were considered. The model selected for evaluating the programme negotiated the sensitive nature and the contextual dimensions of guidance counselling while also ensuring a depth in findings. Underlying the term 'evaluation' in the context of the study was the motivation to seek knowledge, explore and illuminate new learning in the area of guidance counsellor education. Therefore the study can be described as principally an evaluation with illuminative and exploratory characteristics.This paper explores the strengths and limitations of the methodological approach adopted.